Effects of microbial-phytoremediation on plant diversity and soil physico-chemical properties in northern shaanxi coal mining area, china (Bangladesh Journal of Botany, 2023)
Effects of different microorganisms-plant combination on the diversity of plant and soil physics in the mining area were studied. Results showed that the number of species, total number and coverage of Soil Remediation + Vetiver + Sea-buckthorn (AH) treatment were 13, 298 and 89.8%, respectively, which were significantly higher than other treatments. Soil water content in different treatments was the highest at 20 cm. The pH value of the different treatments decreased significantly, and the pH value of AH was the lowest (7.14). The total nitrogen (TN) content of GH and GS were the highest, which were 0.54 and 0.51 g/kg, respectively. The contents of phosphorus (P) and available potassium (K) were the highest in AX treatment, reaching 57.1 and 194 mg/kg. Treatment with different inoculants significantly increased soil enzyme activity. The urease activity of GH was the highest, which was 0.872 mg/g. The sucrase activity and catalase content of AH and AX were the highest, which were 8.99, 8.53 mg/g and 2.145 ml/g, 1.872 ml/g, respectively. The phosphatase activities of QH and AH treatments were the highest at 234 and 229 mg/g, which were 6 times and 5.9 times than that of CK. Comprehensive analysis showed that microbial inoculum + mixed seeding mode can effectively improve soil fertility and enzyme activity, and the effect of AH was the best.Bangladesh J. Bot. 52(2): 495-502, 2023 (June) Special